Physical and Physiological Responses of Cucumber (Cucumis sativus L.) Seeds to Citric Acid Treatment - Dwi Rahmawati; Riska Agustyani (Universitas Muhammadiyah Jember, 2025)
The physical appearance and physiological quality of seeds are critical indicators of cucumber seed quality in horticultural production systems. Improving seed quality requires seed treatments that are both effective and economical, while also ensuring seed viability remains safe. Citric acid has potential as a seed treatment due to its chemical properties and affordability. This research aimed to evaluate the effects of citric acid on cucumber seed quality, focusing on seed lightness, germination performance, and seed vigor. The experiment was conducted from August to November 2023 at PT East West Seed Indonesia, Jember, using a completely randomized design (CRD) with two factors: soaking duration (5, 10, and 15 minutes) and citric acid concentration (1.5%, 2.0%, and 2.5%). The results showed that the highest seed lightness (76.58%) was obtained after 5 minutes of soaking in 1.5% citric acid. The highest germination performance (100%) was achieved with 10 minutes of soaking in 2.0% citric acid, while the highest seed vigor (vigor index 98.67%) was observed at 10 minutes of soaking in 1.5% citric acid. These findings demonstrate that citric acid can improve cucumber seed quality by enhancing physical appearance without compromising physiological performance. Overall, soaking cucumber seeds in 1.5–2.0% citric acid for approximately 10 minutes is recommended as an optimal seed treatment to balance improvements in seed lightness, germination performance, and seed vigor. This research provides an applicable and economical seed treatment strategy for the horticultural seed industry.